Variation in exposure to violence in early adolescence distinguishes between intimate partner violence victimization and perpetration among young men involved in the justice system - Wagers, Shelly M. (Journal of family violence, 2021)
Early exposure to violence (ETV) has been repeatedly linked to violence in intimate relationships later in life. However, this association has rarely been explored among young men involved in the justice system, a group that is of significant policy concern. Methods. Drawing from four waves of data collected from 808 young men with histories of serious offending, this study examined rates of physical and emotional intimate partner violence (IPV) victimization and perpetration. Next, the rates of IPV victimization-perpetration overlap were examined. Lastly, the associations between IPV in young adulthood and ETV in early adolescence were explored using standard difference-in-means tests. Findings show that victimization and perpetration of emotional IPV are common experiences among the men. Seventy-three percent of the sample report emotional IPV victimization and 70% report emotional IPV perpetration. Physical IPV is less common than emotional IPV with 44% of young men reporting being victims of physical IPV and 29% reporting perpetration of physical IPV. Strong linkages were observed between IPV victimization and IPV perpetration. Lastly, associations exist between exposure to violence as a witness or a victim and both emotional and physical IPV victimization and perpetration. IPV involvement as a victim and/or perpetrator is more common than not among young men involved in the justice system. Both emotional and physical forms of IPV are associated with witnessing and experiencing violence during adolescence. Intervention during adolescence is critical to avoid IPV during young adulthood.